Analisis Pengaruh Budaya Organisasi terhadap Kepuasan Kerja dan Kinerja Pegawai di Rumah Sakit Umum Kota Tarakan - Andi Ria Maulina Ghazaly; Syahran Syahran; Isfarudi Isfarudi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Tarakan City General Hospital as a government hospital must provide excellent service to the community who use hospital services. One of the problems faced by the Tarakan City General Hospital related to performance is the problem of organizational culture that has not been fully implemented by the employees of the Tarakan City General Hospital. The purpose of this study is to test and analyze the influence of organizational culture on job satisfaction and employee performance of Tarakan City General Hospital. As well as examining the influence of job satisfaction variables as an intervening variable on organizational culture and employee performance of Tarakan City General Hospital. This study uses a quantitative research approach, with a population of 167 employees of the Tarakan City General Hospital. Meanwhile, the research sample is 37 employees of the medical/clinical personnel section. The analysis technique used uses path analysis with a linear regression analysis approach with the help of SPSS. The results of the study showed that the organizational culture variable had a significant positive influence on job satisfaction at the Tarakan City General Hospital in the medical/clinical staff section. Organizational culture variables have a significant positive influence on employee performance at the Tarakan City General Hospital in the medical/clinical personnel section. The job satisfaction variable has a significant positive influence on employee performance at the Tarakan City General Hospital medical/clinical personnel section. The variable of job satisfaction mediates between organizational culture and employee performance at the Tarakan City General Hospital in the medical/clinical personnel section.